Pengaruh Pembelajaran Inkuiri Berbantuan Media Word Search Puzzle Terhadap Hasil Belajar Siswa Kelas IV Muatan IPA Materi Siklus Hidup di MI Setia Bhakti Trawas - Kholifatur Rosidah; Agung Purwono (Jurnal Riset Madrasah Ibtidaiyah, 2022)
This study aims to determine whether the inquiry learning model assisted by word search puzzle media effect on the learning process concerning life cycle material of science content of the fourth-grade students at MI Setia Bhakti Trawas. This research is kind of an experimental study using two groups pretest-posttest design. The population of this research involved all students of 4th, 5th, and 6th grade. It consisted of 140 students. 40 students of 4th grade were taken as samples using the purposive sampling technique that included 20 students for the experimental class and 20 students for the control class. The data collection technique used was by conducting a test in a form of multiple choice questions. The results of data analysis showed that the learning process of fourth-grade students before and after the method implementation increased from an average of 54,25 to 77.25. Then through the paired sample t-test, the Sig. Of (2tailed) value was obtained over 0.000 < 0.05, while the independent sample t-test obtained 0.002 < 0.05. So it concludes that Ha is accepted, it has a significant effect on inquiry learning assisted by word search puzzle media on the student learning process.